El expediente hagiográfico latino de San Ramón de Roda († 1126) (BHL 7074-7078) - Martín, José Carlos (Analecta Bollandiana, 2023)
This article reviews the Latin texts dedicated to bishop St Raymond of Roda-Barbastro. The study of the manuscript tradition includes the analysis of the main MS: Lérida, Archivo Capitular, Roda 29 (Rc_0029), and its two apographs: Barcelona, Biblioteca de Catalunya, 2564, and Madrid, BN, 1397. But the compositions on St Raymond transmitted in three other codices are also analysed: Città del Vaticano, Archivio Apostolico, Archivum Arcis, Arm. I-XVIII, 4195; Madrid, Biblioteca de la Real Academia de la Historia, 9-5225; and Roma, Accademia Nazionale dei Lincei, 39.D.11 (Cors. 883).